Cain, or the tragic fidelity to earth - Duque, Félix (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Since this is an essay on hermeneutics, this paper says nothing at all about the truth of a text deemed sacred by the three great religions of the Book but is confined to enquire into its context and sound out its assumptions, also relying on Cain, Lord Byron´s unparalleled drama; and all this is intended to bring an entrenched belief in the West´s collective imagination to light, namely, mistrust and contempt for the Earth, that is, for what is opaque, enclosed and retractable, in favour of the heavenly, in other words, of what is open and hierarchically measuring. Such a difference has little to do with the typical metaphysical difference between materialism and spiritualism (or the gnoseological one between realism and idealism); we should rather point out to the difference between what is sacredness and saintliness, that is to say, between what is unyielding to language (yet dormant in it, as an indelible crack) and what is subdued by logos and tamed by it.